The statement that is true about the equation 3(-y + 7) = 3(y + 5) + 6 is;
Statement A; The equation has one solution, y = 0
The given equation is;
3(-y + 7) = 3(y + 5) + 6
Expanding the brackets gives us;
-3y + 21 = 3y + 15 + 6
-3y + 21 = 3y + 21
Using subtraction property of equality, subtract 21 from both sides to give;
-3y = 3y
Using addition property of equality, add 3y to both sides to give;
-3y + 3y = 3y + 3y
6y = 0
Using division property of equality, divide both sides by 6 to get;
y = 0
Read more about factorization at; brainly.com/question/11000698
The missing statements are;
A. The equation has one solution, y = 0.
B. The equation has one solution, y = -1.
C. The equation has no solution.
D. The equation has infinitely many solutions.
1.07 as a percent is 107% 1.07 as a fraction is 1 1/14
Hope this helps!
Step-by-step explanation:
Slope of line ST = Slope of line PQ = -3.
y = -3x + c
When x = 3, y = -1
=> (-1) = -3(3) + c, c = 8
Therefore the equation of line ST is y = -3x + 8 and the y-intercept is 8.
The answer is B, 3/4 is greater than 3/5
3/4=0.75
3/5=0.6
0.75 is greater than 0.6
Answer:
2n + 5
5 times more (add)
Than 2 times the value (multiply)